Forms of disbelonging in contemporary Latin American aesthetics - Garramuño, Florencia (2013)
Literary explorations that juxtapose fiction and photography, images, memories, autobiographies, blogs, chats and email texts, as well as essay and documentary texts that bear witness to a new testimonial condition, are now everywhere, as works as diverse as those by W.G. Sebald, Bernardo de Carvalho, John Berger, João Gilberto Noll, Fernando Vallejo or Nuno Ramos evince. Along with this expansion of literature, in Latin America many of these new literary explorations establish connections among different fields of aesthetics, like the crossover of installation art and literature or language shows in the cases of Nuno Ramos and Mario Bellatin, or the archival impulse that uses images and language in the art of Rosângela Rennó, Antonio José Ponte and Jorge Macchi.